Pengaruh Dekomposisi Ettringite dan Portlandite Terhadap Kekuatan Mekanik Mortar - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Teknik Mesin Fak. Teknik UGM, 2003)
"Mortar, widely used in building construction, is a cement-based substance, which is prepared from portland cement and fine aggregate with a certain composition. In this research, the effect of high temperature on compressive strength of mortar was investigated. Ratio of portland cement to sand was varied from I : 3 to I : 6. After casting, samples were submerged in water for 28 days and then dried in ambient condition. - The samples were exposed to high temperature in an electrical furnace. The temperature was in the range of 200°C to 500"C. For each temperature, in a certain period of time, weight and compressive strength of the samples were determined. A mathematics model was proposed to approach the kinetic of decomposition. The data showed that compressive strength of the samples decreased along heating process. The compressive strength decreased significantly at temperature range of 200°C to 500"C. At 400"C, the compressive strength decreased to about 20% of its initial strength. Meanwhile, at 500°C the samples lost all of their compressive strength. The result also showed that the ratio of portland cement to sand did not have significant contribution to the rate of decreasing of compressive strength of the samples and the rate of decomposition itself. Based on the data, decreasing of compressive strength of the samples was more influenced by the decomposition of portlandite than by the decomposition of ettringite. The proposed mathematics model could be used to approach the kinetic of decomposition. The results also showed that the decomposition process was controlled by diffusion of vapor.